(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The changing dynamics of global trade and increasing demand for efficient supply chainoperations have necessitated a paradigm shift in India’s logistics infrastructure. Multimodal logistics parkshave emerged as a game-changer in optimizing supply chain efficiency, leveraging multiple modes oftransportation, and addressing critical challenges faced by traditional logistics systems. This researchpaper provides a comprehensive analysis of the changing landscape of supply chain in India, focusing onthe significance and impact of multimodal logistics parks in enhancing overall efficiency andcompetitiveness.